2022
DOI: 10.3389/fphar.2022.1056460
|View full text |Cite
|
Sign up to set email alerts
|

Morroniside ameliorates inflammatory skeletal muscle atrophy via inhibiting canonical and non-canonical NF-κB and regulating protein synthesis/degradation

Abstract: No drug options exist for skeletal muscle atrophy in clinical, which poses a huge socio-economic burden, making development on drug interventions a general wellbeing need. Patients with a variety of pathologic conditions associated with skeletal muscle atrophy have systemically elevated inflammatory factors. Morroniside, derived from medicinal herb Cornus officinalis, possesses anti-inflammatory effect. However, whether and how morroniside combat muscle atrophy remain unknown. Here, we identified crucial genet… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
3
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(4 citation statements)
references
References 62 publications
0
3
0
Order By: Relevance
“…Morroniside is an iridoid glycoside and has attracted increasing attention in recent years in terms of its medicinal value. Studies have shown that morroniside can regulate protein expression to improve inflammatory skeletal muscle atrophy [30] and can reduce cartilage destruction by reducing the expression of inflammatory mediators (such as Cox-2, Mmp3, and Mmp13) in articular cartilage [28]. More importantly, it can promote the differentiation of osteoblasts, inhibit the differentiation of osteoclasts, and enhance bone mineral density, to play an anti-osteoporosis role [25], which also provides a certain basis for our study on the anti-inflammatory bone loss of mice using morroniside.…”
Section: Discussionmentioning
confidence: 99%
“…Morroniside is an iridoid glycoside and has attracted increasing attention in recent years in terms of its medicinal value. Studies have shown that morroniside can regulate protein expression to improve inflammatory skeletal muscle atrophy [30] and can reduce cartilage destruction by reducing the expression of inflammatory mediators (such as Cox-2, Mmp3, and Mmp13) in articular cartilage [28]. More importantly, it can promote the differentiation of osteoblasts, inhibit the differentiation of osteoclasts, and enhance bone mineral density, to play an anti-osteoporosis role [25], which also provides a certain basis for our study on the anti-inflammatory bone loss of mice using morroniside.…”
Section: Discussionmentioning
confidence: 99%
“…Morroniside is an iridoid glycoside ( Figure 1 ) and the main active ingredient isolated from Cornus officinalis of the dogwood family Cornaceae [ 183 ]. Morroniside has been shown to exert many biological effects, such as anti-inflammatory, anti-apoptotic, anti-oxidant, cardioprotective and neuroprotective via several mechanisms and signaling pathways, i.e., STAT3, NF-κB, MAPK and PI3K/Akt pathways and molecules regulating the autophagic flux [ 184 , 185 , 186 , 187 , 188 , 189 ]. It has thus long been used to treat degenerative diseases of the nervous system, to inhibit platelet aggregation, to prevent diabetic angiopathies and renal damage, to treat OA and to reduce bone resorption [ 190 ].…”
Section: Plant-derived Compounds With a Reported Senotherapeutic Acti...mentioning
confidence: 99%
“…Morroniside [Cornaceae; Cornus officinalis Siebold and Zucc] (MR), derived from the botanical drug Cornus officinalis, is an iridoid glycoside with many biological effects, such as anti-inflammatory, antioxidant, and anti-apoptotic activities [112]. MR can be used to treat OA by acting through the anti-apoptosis function.…”
Section: Morronisidementioning
confidence: 99%